Teaching English vocabulary to students through online games - Pintado-Peñaloza, Katy Jackeline; Fajardo-Dack, Tammy (Revista Arbitrada Interdisciplinaria Koinonía, 2022)
The objective of this study is to explore the impact of the use of online educational games in comparison with traditional classroom methods to teach English vocabulary to eighth grade students at Mercedes Vázquez Correa School. The quantitative approach was used, with a participation of 13 students for this research. Through a vocabulary retention test, results were obtained showing that students remember a greater amount of vocabulary through traditional methods; however, students remember a greater amount of words accurately with the use of online games. In addition, the survey data reveal that students are comfortable with online games and that they prefer to learn vocabulary through online games rather than through drawings or flashcards in class.